Adolescent Alcohol Exposure Results in Sex-specific Alterations in Conditioned Fear Learning and Memory in Adulthood - Chandler, L. Judson; Vaughan, Dylan T.; Gass, Justin T. (Frontiers in Pharmacology, 2022)
The present study used auditory fear conditioning to assess the impact of repeated binge-like episodes of alcohol exposure during adolescence on conditioned fear in adulthood. Male and female Long-Evans rats were subjected to adolescent intermittent ethanol (AIE) exposure by vapor inhalation between post-natal day 28 and 44. After aging into adulthood, rats then underwent fear conditioning by exposure to a series of tone-shock pairings. This was followed by cued-tone extinction training, and then testing of fear recovery. In male rats, AIE exposure enhanced conditioned freezing but did not alter the time-course of extinction of cued-tone freezing. During subsequent assessment of fear recovery, AIE exposed rats exhibited less freezing during contextual fear renewal, but greater freezing during extinction recall and spontaneous recovery. Compared to males, female rats exhibited significantly lower levels of freezing during fear conditioning, more rapid extinction of freezing behavior, and significantly lower levels of freezing during the tests of fear recovery. Unlike males that were all be classified as high conditioners; female rats could be parsed into either a high or low conditioning group. However, irrespective of their level of conditioned freezing, both the high and low conditioning groups of female rats exhibited rapid extinction of conditioned freezing behavior and comparatively low levels of freezing in tests of fear recovery. Regardless of group classification, AIE had no effect on freezing behavior in female rats during acquisition, extinction, or fear recovery. Lastly, exposure of male rats to the mGlu5 positive allosteric modulator CDPPB prevented AIE-induced alterations in freezing. Taken together, these observations demonstrate sex-specific changes in conditioned fear behaviors that are reversible by pharmacological interventions that target mGlu5 receptor activation.